The Entrepreneurship Potential of Rural Areas: Soap Production as a Side Business for Tanzanian Rice Farmers (AFRICAN JOURNAL OF APPLIED RESEARCH, 2022)
Purpose: This study examines soap production’s entrepreneurship potential and profitability as a supplementary business for rural rice farmers in Tanzania to promote their economic independence.Design/ Methodology/ Approach: We randomly sampled and interviewed about ten small-scale soap manufacturers in urban Tanzania gathered from 2019-2021 to develop a soap production business strategy for rural farmers at a similar scale. Considering the Voronoi theory, we calculated the distance from the rural areas to urban centres to determine the transportation costs, which particularly burden rural farmers. Soap production costs and profitability were determined based on transportation costs and raw material prices.Findings: Rural farmers would incur high transportation costs, given the high average distance to the nearest urban centre (sometimes > 100 km). Nevertheless, producing their rice bran oil, valuable raw material for soap production, would give them a competitive advantage over urban producers.Research Limitation: The study’s proposed strategy can be applied to similar contexts to reduce the urban-rural entrepreneurship divide.Practical Implication: Soaps made using rice bran oil help farmers reuse agricultural waste. Their active ingredients also increase their marketability as high-end cosmetic products, providing farmers with additional income.Social Implication: Commercializing agricultural residues such as rice bran increases farmers’ revenues and reduces CO2 emissions by preventing the residues’ incineration; this creates a virtuous cycle in society.Originality/ Value: This study presents a more realistic business strategy for rural Tanzanian farmers, as, unlike previous studies, it considers not only direct costs but also transportation costs.
Keywords: Entrepreneurship. farmers. production. rice. soap